2019
DOI: 10.1111/bjd.18032
|View full text |Cite
|
Sign up to set email alerts
|

The optimal oral biopsy site for diagnosis of mucous membrane pemphigoid and pemphigus vulgaris

Abstract: Summary Background Accepted ‘standard practice’ for the diagnosis of immunobullous disease is a perilesional sample for direct immunofluorescence (DIF). Objectives To compare diagnostic outcomes of a normal buccal punch biopsy (NBPB) with a perilesional biopsy (PLB) for mucous membrane pemphigoid (MMP) and pemphigus vulgaris (PV). Methods A retrospective analysis of 251 DIF‐positive patients with MMP and 77 DIF‐positive patients with PV was undertaken. Parameters analysed included the intraoral sites of involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 47 publications
1
48
1
5
Order By: Relevance
“…Two oral sites should ideally be sampled: a perilesional biopsy (PLB) for histology and DIF and a second normal buccal punch biopsy (NBPB) also for DIF. We have shown that DIF was positive in 134/143 (93.7%) PLB samples and 129/144 (89.6%) NBPB samples . In those with pure gingival MMP, a biopsy of reflected alveolar mucosa was positive in 100% (17/17).…”
Section: Diagnosismentioning
confidence: 83%
“…Two oral sites should ideally be sampled: a perilesional biopsy (PLB) for histology and DIF and a second normal buccal punch biopsy (NBPB) also for DIF. We have shown that DIF was positive in 134/143 (93.7%) PLB samples and 129/144 (89.6%) NBPB samples . In those with pure gingival MMP, a biopsy of reflected alveolar mucosa was positive in 100% (17/17).…”
Section: Diagnosismentioning
confidence: 83%
“…demonstrates that DIF taken from uninvolved nonperilesional mucosa shows comparable sensitivity to DIF taken from perilesional mucosa for the diagnosis of both PV and multifocal MMP. In pure gingival‐MMP, DIF from the perilesional reflected alveolar mucosa was associated with the highest rate of positive results . Despite the need for further prospective investigations to confirm the highest DIF sensitivity of perilesional vs. lesional biopsies, this study provides a clear recommendation that biopsies from the buccal uninvolved mucosa provide an excellent basis for establishing the diagnosis of an AIBD of the oral mucosa.…”
mentioning
confidence: 73%
“…In this issue of the BJD , Carey and colleagues present an interesting retrospective study that highlights the preferential usage of uninvolved, nonperilesional mucosa as a suitable substrate for direct immunofluorescence (DIF) microscopy for establishing the diagnosis of autoimmune bullous dermatoses (AIBD) affecting the oral mucosa . Oral AIBD comprise a heterogeneous spectrum of conditions, pemphigus vulgaris (PV) and mucous membrane pemphigoid (MMP) being the most common .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If there is oral involvement only and quick access to expertise in taking intraoral biopsies is not available, a 4mm punch biopsy of the buccal mucosa for DIF may suffice, taken by reflecting out the cheek. The sensitivity of DIF on unaffected buccal mucosal has been shown to be 100% in PV . Laboratory expertise will maximize the chance of obtaining a true‐positive DIF result.…”
Section: Investigationsmentioning
confidence: 99%